Paediatric Emergency Nurses’ Perception of Medication Errors: A Qualitative Study - Blanca Collado-González; Ignacio Fernández-López; Valentina Urtubia-Herrera; Ana María Palmar-Santos; Eva García-Perea; María Victoria Navarta-Sánchez (Nursing Reports)
Patient safety is fundamental to healthcare. Adverse events, particularly medication errors, cause harm to patients, especially the paediatric population in the emergency department. Aim: To explore paediatric emergency nurses’ perceptions of medication administration errors. Method: A qualitative, ethnomethodological, descriptive study. The participants were nurses working in the paediatric emergency department. Data were collected through in-depth individual interviews with paediatric emergency nurses. The study excluded nurses employed for less than six months. Ten individual interviews were carried out. All interviews were face-to-face and audio-recorded with the participant’s consent. Interviews took between 52 min and 1 h 25 min. A questions guide was followed during the interviews. The analysis of the data was carried out according to the scheme proposed by Taylor and Bogdan. Results: The participants’ discourse revealed three main categories: Safety culture, transmitted by supervisors and safety groups. Teamwork, with good communication and a positive relationship. Error management, the lack of formal support and negative feelings despite an understanding of the multifactorial nature of errors. The study identifies several challenges in the healthcare system. Emphasis was placed on the perception of errors in terms of patient harm, while near misses or dose delays or omissions are not treated as errors. Conclusions: Although institutions have implemented safety culture strategies, nurses have not fully embraced them. There is a need to promote a positive safety culture and a safe working environment that encourages communication within the team. The hospital should provide training in safe management and patient safety and develop effective protocols. This study was not registered.